2013
DOI: 10.1007/s12040-013-0314-y
|View full text |Cite
|
Sign up to set email alerts
|

Tidal variations in the Sundarbans Estuarine System, India

Abstract: The longer persistence of the high water level around high tide implies that a storm surge is more likely to coincide with the high tide, leading to a greater chance of destruction. Since the stands are associated with an amplification of the 4-hourly and 6-hourly constituents, storm surges that have a similar period are also likely to amplify more during their passage through the SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…As seen before, the time-velocity characteristics of tides in the flood-dominated Hugli estuary are highly asymmetrical and do not observe 6-and 8-hourly rhythm as stated by Rudra (2014) but follow an approximate 3.4-and 9-hourly semidiurnal cycle (Sanyal and Chatterjee, 1995), similar to other estuaries of the Indian GBD (Chatterjee et al, 2013).…”
Section: The Hugli Estuarysupporting
confidence: 57%
“…As seen before, the time-velocity characteristics of tides in the flood-dominated Hugli estuary are highly asymmetrical and do not observe 6-and 8-hourly rhythm as stated by Rudra (2014) but follow an approximate 3.4-and 9-hourly semidiurnal cycle (Sanyal and Chatterjee, 1995), similar to other estuaries of the Indian GBD (Chatterjee et al, 2013).…”
Section: The Hugli Estuarysupporting
confidence: 57%
“…Observations of the spring tides on the Indian side of the Sundarbans Estuarine System, by Chatterjee et al (2013), suggest that the degree and rate of amplification are not uniform and follow a complex pattern along the different distributaries, such that the observed spring tidal range for all coastal stations is always larger than 4.5 m and can be as large as 6.7 m. Results from Kay et al (2015), using a regional ocean model, suggest that the tidal range has little variation along the Sundarbans coastline and over three different epochs in the future up to 2100. SLAMM was developed primarily for the micro-tidal ranges and predominantly diurnal tides in the US and implicitly assumes that mangroves persist from Mean Lower Low Water (mean of the lower low water height each day, hereinafter referred to as MLLW) as the lower elevation boundary for this category up to an elevation equivalent to the Mean High Higher Water (mean of the higher high water height each day, hereinafter referred to as MHHW).…”
Section: Sundarbans Great Diurnal Tidal Range and Mangrove Elevation mentioning
confidence: 99%
“…Chatterjee et al . () provided a comprehensive overview on the observed tidal variations at 30 locations in the Sundarban Estuarine System. Understanding the minute details of variation in amplitude and phase of tides is very essential for proposing navigable inland water routes through the interlaced network of rivers in the head Bay.…”
Section: Introductionmentioning
confidence: 94%
“…Their work reveals that the broad continental shelf and the geometric configuration of the coastline in the head Bay region are responsible for the amplification of semi-diurnal tides. Chatterjee et al (2013) provided a comprehensive overview on the observed tidal variations at 30 locations in the Sundarban Estuarine System. Understanding the minute details of variation in amplitude and phase of tides is very essential for proposing navigable inland water routes through the interlaced network of rivers in the head Bay.…”
Section: Introductionmentioning
confidence: 99%